A case study on a cement treated RAP containing asphalt emulsion and acryl polymer. (December 2018) - Faramarzi, Masoud; Lee, K. Wayne; Kim, Yongjoo; Kwon, Sooahn
Abstract: A Korean contractor developed and used a cement treated Reclaimed Asphalt Pavement (RAP) containing asphalt emulsion and acryl polymer as base layer in Korea. Unfortunately, it was reported that the performance of the mixture was controversial by appearance of reflective and other cracking on the surface of the pavement. In the phase one study, main goals were evaluation of some mechanical properties as well as understanding the material category of this mixture. To achieve these goals, a series of literature reviews and laboratory tests were carried out including Marshall stability and flow, indirect tensile strength, water sensitivity, rutting resistance and compressive strength of both "Contractor mix" and Rhode Island (RI) pavement materials i.e. typical hot mix asphalt (HMA) and Portland Cement Concrete (PCC). According to the Asphalt Pavement Analyzer (APA) test results, it was observed that "Contractor mix" behaved similar to an elastic material at low temperatures while it tends to behave like a visco-elastic material at high temperatures to some extent. Also, it was resistance enough against the moisture damages and rutting phenomena, however, showed considerably lower compressive strength compared to PCC. Because of low compressive strength and probably high shrinkage of this mixture, it could be problematic to use it as base layer material and could affect pavement resistance against some distresses, particularly transverse and reflective cracking. Finally, because of high cement content and rigid behavior it was decided to model this material as concrete and/or cement treated RAP material in the second phase of this study.